1977
DOI: 10.1007/bf00221086
|View full text |Cite
|
Sign up to set email alerts
|

Growth characteristics of postnatal rat adrenal medulla in culture

Abstract: Explants and enzyme-dispersed cells of adrenal medulla from 10-12 day old rats were studied in culture for up to 3 weeks. Adrenomedullary chromaffin cells, nerve cells and satellite cells were clearly discernible. The nerve cells were few in number and did not show catecholaminespecific fluorescence. Chromaffin cells stored catecholamines, as judged by the Falck and Hillarp method, in varying amounts decreasing with age of the cultures and the distance from the explants. Exocytosis profiles observed with the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1978
1978
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(16 citation statements)
references
References 50 publications
2
14
0
Order By: Relevance
“…In confirmation of previous experiments (8,15), the dissociated cells could clearly be identified as chromaffin cells, neurons, or Schwann cells. Chromaffin cells were round after plating and became partially polygonal after 2-3 days in culture.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…In confirmation of previous experiments (8,15), the dissociated cells could clearly be identified as chromaffin cells, neurons, or Schwann cells. Chromaffin cells were round after plating and became partially polygonal after 2-3 days in culture.…”
Section: Resultssupporting
confidence: 88%
“…However, their specific granular vesicles exclusively exhibited highly electron-dense cores, indicating the presence of a primary amine (16). The cores had a diameter of 35-240 nm, which is less than that described for rat adrenal chromaffin cells at the end of the gestation period (17), but which corresponds to the data given for rat adrenal chromaffin cells grown as explants (8).…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Fullydifferentiated (12) showed that chromaffin cells dissociated from the adrenal medulla of infant rats produce fiber outgrowth and exhibit structural, ultrastructural, and biochemical features of sympathetic cells when cultured in a NGF-enriched medium. The property of isolated adrenal medullary cells to occasionally produce neurites even in the absence of NGF had been shown in previous experiments (13,14). The authors attribute the NGF effect to the fact that the dissociated chromaffin cells are not under the influence of glucocorticoids released in the intact gland from adjacent cortical cells.…”
Section: Light and Electron Microscopic Studiesmentioning
confidence: 61%
“…Forty pregnant rats (Sprague-Dawley) raised in our animal quarters were divided into two groups: 26 rats were operated on as indicated below on day 17 of pregnancy (determined on the basis of the observation of the vaginal plug) and 14 rats were housed in single cages. Upon delivery, half of the pups of 10 litters were injected with 10 ,ug of NGF per g body weight, half of the pups of 4 litters with the immunoglobulin fraction of a specific antiserum to NGF (AS-NGF), and the remaining pups of the 14 litters with vehicle solution.…”
Section: Methodsmentioning
confidence: 99%